Method for producing iron-based crystalline alloy

Through the specific composition of iron-based soft magnetic alloy and rapid solidification process, the problem of difficult to achieve high Bs and efficient laminated cores in existing alloys is solved, and efficient BLDC motor applications are achieved.

JP7627981B1Active Publication Date: 2025-02-07NEXT CORE TECHNOLOGIES INC

Patent Information

Application Number
JP2024085418
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2025-02-07
Estimated Expiration
2044-05-27

AI Technical Summary

Technical Problem

The existing Fe-Si-B amorphous alloys and Fe-Si-B-P-Cu nanocrystal alloys are difficult to achieve a saturated flux density of Bs≧1.7T in the high frequency band, and it is difficult to form a stacked core of an efficient BLDC motor, resulting in insufficient motor efficiency and torque.

Method used

A specific iron-based soft magnetic alloy is used to spray liquid alloys on the rotating cooling roller through a rapid solidification process to form alloy sheets with a thickness of 18μm-40μm. The α-Fe phase in the alloy is uniformly distributed to ensure Bs≧1.7T, and mechanical properties are improved through heat treatment.

Benefits of technology

The saturated magnetic flux density of Bs≧1.7T is achieved, which reduces iron loss and can form an efficient laminated core. It is suitable for high-frequency BLDC motors and improves motor efficiency and torque.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627981000001_ABST
    Figure 0007627981000001_ABST
Patent Text Reader

Abstract

To provide an iron-based soft magnetic alloy having Bs≧1.7T and low core loss performance, which can be made into a laminated core. In an iron-based soft magnetic alloy, the composition formula (Fe 1-m Co m ) 100-x-y S x (B 1-n C n ) y wherein the composition ratios x, y, m and n satisfy 1.0≦x≦3.0 atomic %, 11.0≦y≦14.0 atomic %, 0.05≦m≦0.5 and 0.0≦n≦0.3, respectively; the iron-based soft magnetic alloy has a metal structure consisting of an α-Fe phase, a ratio of an amorphous phase is 20 volume % or less, a saturation magnetic flux density is 1.7 T or more and 2.0 T or less, an iron loss at a magnetic flux density of 1.5 T and a frequency of 1 kHz is 50 W / kg or less, and a thickness of the iron-based soft magnetic alloy is 18 μm or more and less than 40 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an iron-based crystalline alloy. Gold More specifically, the manufacturing method is an iron-based crystal alloy that can be applied to various brushless DC motors. Gold It relates to a manufacturing method. [Background technology]

[0002] In recent years, there has been a demand from the market for materials with low iron loss and high saturation magnetic flux density for various passive elements and transformers in the power electronics field, such as inductors and reactors used as electronic components. There is an increasing demand for iron-based amorphous materials, which are soft magnetic materials with high magnetic permeability and low iron loss, and Fe-Si-B rapidly solidified alloy thin ribbons with a thickness of approximately 17 μm to 25 μm, which are produced by rapid solidification of a molten metal made primarily of iron (Fe), silicon (Si), and boron (B), such as iron-based nanocrystalline materials, as low iron loss soft magnetic materials to replace conventional silicon steel sheets (Fe-Si), for use in large transformers and inductors.

[0003] In addition, the Fe-Si-B-based rapidly solidified alloys have been considered for use in the stator cores of brushless direct current (BLDC) motors, taking advantage of their low iron loss compared to silicon steel sheets, and for the purpose of reducing the iron loss in the stator cores and increasing the efficiency of brushless direct current (BLDC) motors. In particular, in high-speed motors that exceed 10,000 rpm or 20,000 rpm, the operating range of soft magnetic materials is a high-frequency band of 1 kHz or more, so it has been confirmed that the iron loss in the stator cores is suppressed and unprecedented high efficiency can be achieved. Furthermore, in the current situation where about 60% of the world's electricity is consumed by motors, increasing the efficiency of motors is expected to be a direct means of achieving carbon-free society, and it is expected that this will be used in electric vehicles, white goods such as air conditioners, and motors for factory automation.

[0004] However, the above Fe-Si-B amorphous alloy has a saturation magnetic flux density of 1.6 T or less, which is lower than the 1.8 T of electromagnetic steel sheets, which are currently used as motor core materials, and so while it can ensure the necessary motor output in high-speed motors of 10,000 rpm or more, it is difficult to apply it to motors that require high torque from low rotation speeds, such as factory automation and air mobility. For this reason, there is a demand for an iron-based soft magnetic material that can achieve both low iron loss performance comparable to that of Fe-Si-B amorphous alloys while ensuring a high saturation magnetic flux density of about 1.8 T, which is comparable to that of electromagnetic steel sheets.

[0005] Due to the above market demands, it is difficult for Fe-Si-B based amorphous alloys, which have a maximum Bs of around 1.6 T, or iron-based nanocrystalline materials (such as FINEMETR), which have a Bs of around 1.4 T, to replace electromagnetic steel sheets with a Bs of 1.8 T. To date, there have been no examples of BLDC motors using Fe-Si-B based rapidly solidified alloys being brought to the market as motors for factory automation or air mobility.

[0006] Until now, BLDC motors for the above-mentioned factory automation and air mobility have combined magnetic steel sheet core materials with anisotropic rare earth iron boron sintered magnets, which exhibit excellent permanent magnetic properties, to achieve high efficiency by utilizing magnet torque. However, with magnetic steel sheets, which have high iron loss, the input power is lost through iron loss generated in the stator core, making it impossible to obtain the motor efficiency required for BLDC motors for factory automation and air mobility. Therefore, there is extremely high market demand for high-output, high-efficiency BLDC motors that can contribute to energy savings in a variety of applications.

[0007] Furthermore, Fe-Si-B amorphous alloys can significantly reduce iron loss to less than one-tenth that of electromagnetic steel sheets, and because they also have high magnetic permeability, if they can overcome the issue of lower Bs than electromagnetic steel sheets, then it will be possible to ensure the motor output required for BLDC motors for factory automation and air mobility by achieving Bs ≥ 1.7 T. For this reason, there are extremely high expectations worldwide from the motor market for core materials that achieve low iron loss on a par with iron-based amorphous alloys that can achieve Bs ≥ 1.7 T, making them an alternative to electromagnetic steel sheets.

[0008] The electromagnetic steel sheets used in the rotor cores and stator cores of BLDC motors are used as laminated cores, but existing Fe-Si-B amorphous alloys are difficult to punch due to their thin thickness of about 20 μm. In addition, because the alloy is thin, the space factor when made into a laminated core is low (less than 90%) compared to the 92% or more of electromagnetic steel sheets, due to the thin alloy thickness. This makes it difficult to obtain motor torque on a par with that of electromagnetic steel sheets.

[0009] In Non-Patent Document 1, it is stated that Fe-Si-B amorphous alloys have been 4 ~10 6 It has been disclosed that an amorphous structure can be obtained only when the rapidly solidified alloy ribbon has a thickness of about 17 to 22 μm and is rapidly solidified at an extremely fast rapid solidification rate of, for example, 100,000 sec., but that it is possible to obtain an iron-based amorphous alloy ribbon with a thickness of 50 μm or more by slowing down the rapid solidification rate by adding phosphorus (P). However, not only does the addition of P cause a decrease in the saturation magnetic flux density Bs, but in the case of P-added alloys, the P component volatilizes during alloy melting, causing significant contamination inside the furnace, and therefore there are still few examples of its application in the industrial field.

[0010] Non-Patent Document 2 discloses that the Fe-Si-B-P-Cu system iron-based nanocrystalline alloy "NANOMETR" is a soft magnetic material that has a high saturation magnetic flux density Bs: 1.85 T and low iron loss performance comparable to that of an iron-based amorphous alloy. However, this iron-based nanocrystalline alloy is very brittle and difficult to form into a laminated core by punching and pressing, making it difficult to apply it to the rotor cores and stator cores of BLDC motors at the mass-production level. Therefore, except at the prototype level, there have been no examples of it being used practically as a core material for motors.

[0011] Patent Documents 1, 2, and 3 describe methods for producing rapidly solidified alloy ribbons with a thickness of 50 μm or more. However, none of them have produced an Fe-Si-B-based amorphous alloy with Bs ≧ 1.7 T that is intended for application to laminated cores for BLDC motors for driving EVs, and there are no examples yet of industrial use of iron-based amorphous alloys as soft magnetic materials to replace silicon steel sheets.

[0012] Patent Document 4 discloses a method for producing a metal ribbon, characterized in that molten metal is ejected from a plurality of openings (multi-hole nozzles) arranged on a moving cooling substrate (rotating cooling roll) at a substantially right angle to the direction of movement of the substrate and each of which has an angle of 10 to 80° to the direction of movement, and then rapidly cooled and solidified. However, Patent Document 4 is an invention made for the purpose of reducing the variation in thickness of a metal ribbon in the width direction when producing a wide rapidly cooled ribbon. In addition, it is difficult to process a plurality of openings having an elongated parallelogram, trapezoid, or ellipse shape with angles of 10 to 80°, and there is also a problem of high nozzle processing costs, making it difficult to use on an industrial mass production level.

[0013] Patent Document 5 discloses a method for producing an Fe-Si-B based amorphous alloy having a thickness of 40 μm or more, but does not disclose an alloy composition that can ensure Bs≧1.7 T, and does not aim to provide a soft magnetic material for BLDC motors for driving EVs.

[0014] Patent Document 6 describes an Fe-Si-B based rapidly solidified alloy having a thickness of 40 μm to 70 μm and a saturation magnetic flux density Bs≧1.7 T and a coercive force Hc≦200 A / m, and a method for producing the same. However, during the rapid solidification process, 0.1 vol % to 10 vol % of an α-Fe phase precipitates in the surface layer, and the remainder of the rapidly solidified alloy is an amorphous structure. This may make it difficult to perform punching press processing depending on the core shape. [Prior art documents] [Patent documents]

[0015] [Patent Document 1] Patent Publication No. 5-329587 [Patent Document 2] JP 7-113151 [Patent Document 3] Patent Publication No. 8-124731 [Patent Document 4] Patent Publication No. 63-220950 [Patent Document 5] Patent Publication No. 2018-153828 [Patent Document 6] Patent Publication No. 2021-193199 [Non-patent literature]

[0016] [Non-Patent Document 1] Creation of new bulk metallic glass / amorphous thick plates with high saturation magnetic flux density (Tohoku University, Metallic Glass Research Center) Akihiro Makino, Ken Kubota, Tono Chuntao [Non-Patent Document 2] Latest research and development trends of ultra-low core loss, high iron content soft magnetic alloy "NANOMET", Journal of the Japan Society for Metals Material, Vol. 55, No. 3 (2016) Summary of the Invention [Problem to be solved by the invention]

[0017] Fe-Si-B-based rapidly solidified alloys are expected to have low core loss performance comparable to that of Fe-Si-B-based amorphous alloys, which can significantly improve motor efficiency while maintaining a saturation magnetic flux density at the same level as electromagnetic steel sheets that are widely used for transformers and various motors, and can be punched by press like electromagnetic steel sheets, and can ensure a core space factor of 90% or more, and can be used as laminated cores for motors. However, it is difficult to ensure a saturation magnetic flux density at the same level as electromagnetic steel sheets with Fe-Si-B-based amorphous alloys. On the other hand, the Fe-Si-B-based rapidly solidified alloy described in Patent Document 6, which contains a mixture of amorphous structure and a crystalline phase consisting of α-Fe, can ensure a saturation magnetic flux density Bs ≧ 1.7 T, but it is difficult to punch it at a press speed at the same level as electromagnetic steel sheets. For this reason, it has been difficult to use it as a core for BLDC motors for factory automation, air mobility, etc.

[0018] Therefore, the present invention provides an iron-based soft magnetic alloy that has Bs≧1.7T and low core loss performance and can be made into a laminated core. Gold The purpose is to provide a manufacturing method. [Means for solving the problem]

[0019] The iron-based soft magnetic alloy according to the present invention The method of producing gold is Composition formula (Fe 1-m Co m ) 100-x-y S x (B 1-n C n ) y The composition ratios x, y, m, and n satisfy the following conditions: 1.0≦x≦3.0 atomic %, 11.0≦y≦14.0 atomic %, 0.05≦m≦0.5, and 0.0≦n≦0.3, respectively. and a rapid solidification step of rapidly solidifying the molten alloy on a cooling roll made of any one of pure copper, a copper alloy, Mo, and W as a main raw material. It has a metal structure consisting of an α-Fe phase, the ratio of the amorphous phase is 20 volume % or less, the saturation magnetic flux density is 1.7 T or more and 2.0 T or less, and the iron loss at a magnetic flux density of 1.5 T and a frequency of 1 kHz is 50 W / kg or less. , Thickness Iron-based soft magnetic alloy with a cracking thickness of 18 μm or more and less than 40 μm the rapid solidification step includes a step of injecting the molten alloy from a nozzle onto a surface of the chill roll while rotating the chill roll at a roll surface speed of 15 m / sec or more and 50 m / sec or less, the nozzle is a single slit nozzle arranged so that a longitudinal direction of the slit is perpendicular to a rotation direction of the chill roll, the nozzle is made of a material mainly composed of any one of quartz (SiO2), boron nitride (BN), silicon carbide (SiC) and alumina (Al2O3), the nozzle opening width is 0.2 mm or more and 0.8 mm or less, the chill roll has a surface roughness of arithmetic mean roughness (Ra) of 0.01 μm or more and 0.6 μm or less, the distance from the nozzle to the chill roll is 0.1 mm or more and 2.0 mm or less, and the molten alloy is discharged from the nozzle at a pressure of 5 kPa or more and 50 kPa or less. It is characterized by:

[0020] This iron-based soft magnetic alloy preferably has an iron loss of 1500 W / kg or less at a magnetic flux density of 1.5 T and a frequency of 20 kHz.

[0021] In addition, in this iron-based soft magnetic alloy, the average crystal grain size of the α-Fe phase is preferably 5 nm or more and less than 100 nm. Effect of the Invention

[0027] According to the present invention, an iron-based soft magnetic alloy having Bs≧1.7T and low core loss performance and capable of being formed into a laminated core is provided. Gold A method of manufacture may be provided. [Brief description of the drawings]

[0028] [Figure 1] FIG. 1A is a schematic diagram of an apparatus for producing an iron-based soft magnetic alloy according to an embodiment of the present invention, FIG. 1B is an enlarged view of a main portion thereof, and FIG. [Diagram 2] 1 is a powder X-ray diffraction profile of the iron-based soft magnetic alloy obtained in Example 2. [Diagram 3]1 is a powder X-ray diffraction profile of the iron-based soft magnetic alloy obtained in Example 7. [Figure 4] 1 shows X-ray diffraction profiles of the free surface (opposite side to the contact surface with the chill roll) and the chill roll surface of the Fe—Si—B rapidly solidified alloy obtained in Comparative Example 12. [Diagram 5] 1 shows X-ray diffraction profiles of the free surface (opposite side to the contact surface with the chill roll) and the chill roll surface of the Fe—Si—B rapidly solidified alloy obtained in Comparative Example 13. [Figure 6] 1 is a plot of the relationship between magnetic flux density and core loss for each operating frequency in the iron-based soft magnetic alloy obtained in Example 2. [Figure 7] 1 is a plot of the relationship between magnetic flux density and core loss for each operating frequency in the Fe—Si—B rapidly solidified alloy obtained in Comparative Example 12. [Figure 8] 1 shows the relationship between the operating frequency and the iron loss at a magnetic flux density of 1.5 T for Example 2, Comparative Example 12, and a commercially available electrical steel sheet (35A360 manufactured by JFE Corporation). [Figure 9] 3 is a SEM photograph of the iron-based soft magnetic alloy of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] The iron-based soft magnetic alloy of the present invention has low iron loss performance that is equal to or better than that of Fe-Si-B amorphous alloys, with iron loss that is 1 / 10 or less than that of electromagnetic steel sheets.However, by isotropically and uniformly precipitating fine crystals made of α-Fe in the rapid solidification process during production, the iron-based soft magnetic alloy has an average thickness of 18 μm or more and less than 40 μm, and can be used to mass-produce laminated cores with a press punching efficiency at the same level as that of electromagnetic steel sheets, while ensuring a saturation magnetic flux density Bs ≧ 1.7 T that is applicable to BLDC motors for factory automation and air mobility, etc.

[0030] As described above, the inventors of the present invention have discovered that an iron-based soft magnetic alloy can be obtained that has low iron loss performance equivalent to or better than that of an Fe-Si-B amorphous alloy, and that can be used to mass-produce laminated cores with a press punching efficiency equivalent to that of electromagnetic steel sheets, while maintaining a saturation magnetic flux density Bs≧1.7T that is applicable to BLDC motors for factory automation, air mobility, and the like, in a pseudo ternary composition region of the essential elements Fe+Co, Si, and B, with the compounding ratios of each element being 1.0 atomic % or more and 3.0 atomic % or less of Si, 11 atomic % or more and 14 atomic % or less of B, with 5% or more and 50% or less of Fe being replaced with Co, and with a portion of B being replaced with C up to an upper limit of 30%, and that can obtain an iron-based soft magnetic alloy that has low iron loss performance equivalent to that of an Fe-Si-B amorphous alloy, and that can be used to mass-produce laminated cores with a press punching efficiency equivalent to that of electromagnetic steel sheets, and has thus arrived at the present invention.

[0031] [Alloy composition] By using Fe as an essential element to account for the remainder of the above elements and substituting a portion of Fe with Co, which is a ferromagnetic element like Fe, Bs≧1.7T can be ensured. However, if the substitution rate m of Co for Fe is less than 5%, Bs≧1.7T cannot be ensured. Furthermore, if the substitution rate m of Co for Fe exceeds 50%, Bs tends to decrease. For this reason, the substitution rate m of Co for Fe is limited to 5% or more and 50% or less. The substitution rate m is preferably 10% or more and 40% or less, and more preferably 15% or more and 35% or less from the viewpoint of cost-effectiveness.

[0032] In the present invention, Si is not only an essential element for obtaining a fine structure, but also plays an important role in expressing soft magnetic properties such as magnetic permeability. If the composition ratio x of Si is less than 1.0 atomic %, not only the magnetic permeability at an applied magnetic field of 10 A / m deteriorates to 2000 or less, but also the core loss at 1 kHz and 1.5 T becomes 100 W / kg or more, so that the characteristics of the iron-based soft magnetic alloy of the present invention, that is, high magnetic permeability and low core loss compared to electromagnetic steel sheets, are reduced. Furthermore, if the composition ratio x of Si exceeds 3.0 atomic %, the abundance ratio of Fe, which is responsible for magnetization, decreases and Bs≧1.7 T cannot be obtained. For this reason, the composition ratio x of Si is set to 1.0 atomic % or more and 3.0 atomic % or less. The composition ratio x of Si is preferably 1.2 atomic % or more and 2.5 atomic % or less, and more preferably 1.3 atomic % or more and 2.2 atomic % or less.

[0033] If the composition ratio y of B+C is less than 11.0 atomic %, the metal structure of the iron-based soft magnetic alloy obtained by rapid solidification becomes coarse, and not only is it not possible to ensure low iron loss performance of 50 W / kg or less at a magnetic flux density of 1.5 T and a frequency of 1 kHz, but also the iron-based soft magnetic alloy is prone to cracking during the punching process by pressing, making it difficult to form a laminated core. Also, if the composition ratio y of B+C exceeds 14.0 atomic %, the abundance ratio of Fe, which is responsible for magnetization, decreases and Bs≧1.7 T cannot be obtained. For this reason, the composition ratio y of B+C is 11.0 atomic % or more and 14.0 atomic % or less. The composition ratio y of B+C is preferably 11.5 atomic % or more and 13.5 atomic % or less, and more preferably 12.0 atomic % or more and 13.5 atomic % or less.

[0034] By replacing a portion of B with C, the melting point of the molten alloy is lowered, the rapid solidification conditions are relaxed, and the iron-based soft magnetic alloy of the present invention is easier to produce, but if the substitution rate n of C for B exceeds 30%, Bs≧1.7T cannot be ensured, which is not preferable. For this reason, the substitution rate n is limited to 30% or less. From the viewpoint of achieving both high Bs characteristics and low magnetic permeability, the substitution rate n is preferably 20% or less, and more preferably 15% or less.

[0035] In the iron-based soft magnetic alloy of the present invention, A l、V, Ti, Mn 、Z It is possible to add one or more additive elements selected from the group consisting of N, Ga, Zr, Nb, Mo, Ag, Hf, Ta, W, Pt, Au, and Pb. However, if the additive concentration exceeds 2.0 atomic %, Bs≧1.7T cannot be obtained, so this is not preferable. It is permissible to add the additive element within 2.0 atomic %, including the inclusion of the element as an impurity.

[0036] [Metal structure] The iron-based soft magnetic alloy of the present invention is characterized by being composed of an α-Fe phase that precipitates isotropically without being oriented in a specific direction. The fine α-Fe crystal phase that precipitates isotropically throughout the iron-based soft magnetic alloy is a fine crystalline structure with an average crystal grain size of 5 nm or more and less than 100 nm. The average crystal grain size of the α-Fe phase can be determined from the half-width of the X-ray diffraction peak by powder X-ray diffraction (XRD) as described below.

[0037] However, even if an amorphous phase is present in the metal structure of the iron-based soft magnetic alloy obtained when the molten alloy is rapidly solidified on a rotating cooling roll, the amount is acceptable as long as it does not adversely affect the soft magnetic properties. If the amorphous phase in the metal structure of the iron-based soft magnetic alloy exceeds 20 volume % of the entire metal structure, it becomes difficult to achieve Bs≧1.7T, so the content of the amorphous phase is 20 volume % or less. The content of the amorphous phase is preferably 10 volume % or less, and more preferably 5.0 volume % or less.

[0038] When the iron-based soft magnetic alloy of the present invention is mass-produced and applied to laminated cores, it is necessary to continuously punch the iron-based soft magnetic alloy by a press to match the shape of a rotor core, a stator core, etc., but in the rapid solidification process during the manufacture of the iron-based soft magnetic alloy, the presence of coarse α-Fe crystal phases oriented in the (200) direction (in-plane orientation) with an average crystal grain size of 100 nm or more precipitated by heterogeneous nucleation during rapid solidification near the surface of the quench roll or free surface may become the starting point of cracks during punching, making punching difficult. For the above-mentioned reasons, if the coarse α-Fe crystal phases oriented in the (200) direction exceed 10.0 volume % of the entire metal structure, cracks and chips may occur in the iron-based soft magnetic alloy during punching, so the α-Fe crystal phase precipitated on the surface layer of the iron-based soft magnetic alloy is preferably 10 volume % or less, and from the viewpoint of stable punching workability, it is preferably 5.0 volume % or less, and more preferably 2.0 volume % or less. In the present invention, the surface layer refers to a depth from the surface of the iron-based soft magnetic alloy that is within a range of 10% of the thickness of the iron-based soft magnetic alloy.

[0039] [Magnetic properties] The saturation magnetic flux density Bs of the iron-based soft magnetic alloy of the present invention is 1.7 T or more and 2.0 T or less in the state immediately after rapid solidification (as-spun) or after heat treatment at a temperature of 180 ° C or more and less than 450 ° C for the purpose of removing distortion from the as-spun state. If Bs exceeds 2.0 T, the iron loss at a magnetic flux density of 1.5 T and a frequency of 1 kHz exceeds 50 W / kg, so that when applied to a core for a BLDC motor for FA and air mobility, etc., a clear improvement in motor efficiency is not obtained compared to a core made of electromagnetic steel sheet. From the viewpoint of achieving both a necessary and sufficient motor torque and high efficiency in the low rotation speed range, Bs is 1.7 T or more and 2.0 T or less, preferably 1.73 T or more and 1.97 T, and more preferably 1.75 T or more and 1.95 T or less.

[0040] In addition, while the iron loss value of existing magnetic steel sheets, iron-based amorphous alloys, and iron-based nanocrystalline alloys shows a tendency to increase with increasing magnetic flux density at each operating frequency, the iron-based soft magnetic alloy of the present invention shows a very unique magnetic property in that the iron loss value of each operating frequency shows a clear tendency to saturate with increasing magnetic flux density. In particular, the iron loss value at a magnetic flux density of 1.5T at a frequency of 20kHz, which is a high frequency range, is 1500W / kg or less, and there is a possibility that the iron loss that is a problem in ultra-high speed rotating motors of 50,000 rpm or more and transformers of voltage step-up units can be significantly reduced. If the iron loss value at a magnetic flux density of 1.5T at a frequency of 20kHz is too high (for example, 2000W / kg or more), the iron loss will be at the same level as that of iron-based amorphous alloys and iron-based nanocrystalline alloys, so the iron loss value at a magnetic flux density of 1.5T at a frequency of 20kHz is preferably 1500W / kg or less, more preferably 1300W / kg or less, and even more preferably 1000W / kg or less.

[0041] [Method of manufacturing iron-based crystalline alloy] The iron-based soft magnetic alloy of the present invention is produced by a method for producing an iron-based crystalline alloy, which includes a step of preparing a molten alloy having the above-mentioned composition, and a step of rapidly solidifying the prepared molten alloy by rapidly cooling.

[0042] Fig. 1(a) is a schematic diagram of a single-roll molten metal quenching apparatus used in a method for producing an iron-based soft magnetic alloy according to an embodiment of the present invention, Fig. 1(b) is an enlarged view of a nozzle, and Fig. 1(c) is an enlarged view of the nozzle bottom. The single-roll molten metal quenching apparatus 1 shown in Fig. 1 includes a melting furnace 2, a molten metal storage vessel 5, and a cooling roll 8.

[0043] The melting furnace 2 supplies molten alloy 3, obtained by melting raw materials by high-frequency induction heating, to a molten metal storage container 5 by rotating a tilting shaft 4. The molten metal storage container 5 is equipped with a nozzle 6 at its bottom, and the molten alloy 3 is further heated by a heating coil (not shown) and ejected from a slit 7 formed at the lower end of the nozzle 6 onto the surface (outer circumferential surface) of a chill roll 8. Cooling water is supplied to the inside of the chill roll 8 to rapidly cool the molten alloy that comes into contact with the surface, forming a ribbon-like rapidly solidified alloy 9. The nozzle 6 is made of a material such as quartz (SiO2 ), boron nitride (BN), silicon carbide (SiC) and alumina (Al 2 O 3 ) can be appropriately selected as the main component.

[0044] The nozzle 6 is a single slit nozzle in which a single slit 7 is formed, and the longitudinal direction of the slit 7 is arranged so as to be perpendicular to the rotation direction of the chill roll 8 (i.e., parallel to the rotation axis of the chill roll 8). The width W1 of the slit 7 plays a role in adjusting the rate of discharge of the molten alloy 3 supplied to the chill roll 8. If the slit width W1 is too small, slit processing is likely to become difficult, and furthermore, the slit 7 is likely to be blocked by the molten alloy. On the other hand, if the slit width W1 is too large, the discharge rate becomes too high, and the heat removal by the chill roll 8 is not kept up, and the rapidly solidified alloy sticks to the chill roll 8, making it difficult to continue stable molten rapid solidification. Therefore, the slit width W1 is 0.2 mm or more and 0.8 mm or less. The slit width W1 is preferably 0.3 mm or more and 0.7 mm or less, and more preferably 0.3 mm or more and 0.6 mm or less.

[0045] The molten metal supplied to the surface of the chill roll 8 becomes a ribbon-shaped rapidly solidified alloy 9 by the rotation of the chill roll 8, and is peeled off from the chill roll 8. If the surface speed of the chill roll 8 is less than 15 m / sec, the rapidly solidified alloy becomes excessively thick, 40 μm or more, and the α-Fe crystal phase having an average crystal grain size of 100 nm or more and oriented in the (200) direction, which is precipitated by non-uniform nucleation during rapid solidification, may exceed 10.0 vol.% near the surface of the chill roll surface or free surface of the iron-based soft magnetic alloy ribbon, and cracks or chips may easily occur in the iron-based soft magnetic alloy during punching. On the other hand, if the surface speed of the chill roll 8 exceeds 50 m / sec, the thickness of the iron-based soft magnetic alloy ribbon becomes 18 μm or less, making it difficult to ensure a core space factor of 90% or more when it is made into a laminated core. Therefore, the surface speed of the cooling roll 8 is 15 m / sec or more and 50 m / sec or less, preferably 20 m / sec or more and 45 m / sec or less, and more preferably 25 m / sec or more and 40 m / sec or less.

[0046] 1(a), if the distance d from the tip of the nozzle 6 to the surface of the chill roll 8 is too small, the quenched alloy may stick to the chill roll 8, making it difficult to continue stable quenching and solidification of the molten alloy 3, whereas if the distance is too large, a puddle may not be formed on the surface of the chill roll 8, making it difficult to rapidly solidify the molten alloy 3. For this reason, the distance d is 0.1 mm or more and 2.0 mm or less, preferably 0.1 mm or more and 1.5 mm or less, and more preferably 0.15 mm or more and 1.0 mm or less.

[0047] In producing the ribbon-shaped rapidly solidified alloy 9, the adhesion of the molten alloy 3 to the outer surface of the chill roll 8 is important, but this adhesion of the molten alloy is largely dependent on the surface roughness of the chill roll 8. If the surface roughness of the chill roll 8 is too small, the molten alloy 3 will slip on the surface of the chill roll 8, making sufficient cooling difficult, whereas if the surface roughness of the chill roll 8 is too large, the quenched alloy may stick to the chill roll 8. For this reason, the arithmetic mean roughness (Ra) of the surface of the chill roll 8 is 0.01 μm or more and 0.6 μm or less, preferably 0.05 μm or more and 0.55 μm or less, and more preferably 0.1 μm or more and 0.5 μm or less.

[0048] The chill roll 8 is preferably made of a material whose main raw material is any one of pure copper, copper alloy, molybdenum (Mo) and tungsten (W), thereby providing excellent thermal conductivity and durability. The main raw material means that it accounts for 50% or more by weight. The surface of the chill roll 8 may be plated with chromium, nickel or an alloy of these, which increases the heat resistance and hardness of the surface of the chill roll 8 and suppresses melting and deterioration of the roll surface during rapid solidification.

[0049] The diameter of the chill roll 8 is, for example, 200 to 20,000 mm. The chill roll 8 does not necessarily need to be water-cooled if the continuous quenching and solidification time is short, such as 10 seconds or less, but if the continuous quenching and solidification time is 10 seconds or more, it is preferable to suppress a temperature rise on the surface of the chill roll 8 by running cooling water inside the chill roll 8. It is preferable to appropriately adjust the water-cooling capacity of the chill roll 8 according to the latent heat of solidification and the molten metal tapping rate per unit time.

[0050] [Heat treatment] In a preferred embodiment, the iron-based soft magnetic alloy is heat-treated at a constant temperature of 180°C to 450°C after rapid solidification or punching press, thereby making it possible to remove distortion in the iron-based soft magnetic alloy and further improving the magnetic permeability. If the heat treatment temperature is less than 180°C, the effect of removing distortion is reduced, while if it exceeds 450°C, the iron loss tends to increase due to the crystal grain growth of α-Fe constituting the iron-based soft magnetic alloy. The heat treatment temperature is preferably 200°C to 400°C, more preferably 200°C to 350°C. The heat treatment is preferably performed in a vacuum or inert gas atmosphere, but heat treatment in the air is also acceptable as long as it is 350°C or less.

[0051] In addition, the heat treatment may be performed in a state where a plurality of iron-based soft magnetic alloy ribbons are overlapped and adhered to each other. An adhesive resin may be applied to the adhesion surfaces of the overlapped iron-based soft magnetic alloy ribbons, and a thermocompression bonding process may be performed within the above-mentioned heat treatment temperature range to obtain a multi-layer bonded iron-based soft magnetic alloy at the same time as the heat treatment.

[0052] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.

[0053] 100 kg of raw materials containing B, C, Co, and Fe with a purity of 99.5% or more were placed in an alumina crucible (melting furnace) and melted by high-frequency induction heating to form a molten alloy, so as to obtain the alloy compositions shown in Examples 1-11 and Comparative Examples 12-15 in Table 1 below. 50 kg of this molten alloy was poured into an alumina storage vessel with an inner diameter of 200 mm and a height of 400 mm and a single slit nozzle made of BN at the bottom. The slit width and slit length of the nozzle are as shown in Table 1.

[0054] Then, the 50 kg of molten alloy was further heated by passing electricity through a high-frequency heating coil installed around the molten alloy storage vessel. After the temperature of the molten alloy reached a temperature approximately 100°C higher than the melting point of the alloy composition, the alumina molten alloy stopper placed on the top of the nozzle was pulled out, and the molten alloy was sprayed from the nozzle onto the surface of the chill roll directly below. The chill roll was made of chrome zirconium copper, with an outer diameter of 600 mm and a width of 200 mm. The gap between the nozzle and the chill roll surface is as shown in Table 1. The spray pressure of the molten alloy from the nozzle, the roll surface speed of the chill roll, and the arithmetic mean roughness (Ra) of the roll surface of the chill roll are as shown in Table 2.

[0055] The molten alloy ejected onto the surface of the chill roll formed a puddle on the surface of the chill roll and was rapidly solidified at the interface between the puddle and the chill roll, obtaining a ribbon-shaped rapidly solidified alloy (iron-based soft magnetic alloy in the examples) having the average thickness and average width shown in Table 3. The rapidly solidified alloy obtained was subjected to a punching test 10 times using a punch with a diameter of 1 mm, and the results of checking whether cracks occurred in the iron-based soft magnetic alloy during the test are shown in Table 3.

[0056] The structure of the rapidly solidified alloys was evaluated by powder X-ray diffraction (XRD), and it was found that the iron-based soft magnetic alloys of Examples 1 to 11 all had a metal structure in which the α-Fe phase was isotropically precipitated without being oriented in a specific direction. The volume ratio of the amorphous phase calculated from the powder X-ray diffraction results is shown in Table 3.

[0057] As representative examples, X-ray diffraction profiles evaluated from the free surface side of the iron-based soft magnetic alloy ribbon for Example 2 and Example 7 are shown in Figures 2 and 3, respectively. In both Figures 2 and 3, the main peak of α-Fe, (110), and the secondary peak, (200), were confirmed, and both were diffraction peaks with wide half-widths, confirming a fine metal structure consisting of an isotropically precipitated α-Fe crystal phase.

[0058] Among the iron-based soft magnetic alloys of Examples 1-11, the iron-based soft magnetic alloys except for Example 10 were measured immediately after rapid solidification, and the iron loss at 20 kHz at 1.5 T was measured after heat treatment. The results are shown in Table 4. Bs was measured using a vibration type sample magnetometer manufactured by Toei Kogyo Co., Ltd., and μ and iron loss were measured using a BH analyzer manufactured by Iwasaki Electric Co., Ltd., with an SST unit (single sheet magnetic property tester). As a representative example of an example showing the relationship between magnetic flux density and iron loss, the iron-based soft magnetic alloy of Example 2 is plotted for each operating frequency in FIG. 6.

[0059] On the other hand, the Fe-Si-B rapidly solidified alloys of Comparative Examples 12-15 were found to be dominated by the amorphous phase by powder X-ray diffraction (XRD). As representative examples, the X-ray diffraction profiles evaluated from the free surface side of the rapidly solidified alloy ribbons for Comparative Examples 12 and 13 are shown in Figs. 4 and 5, respectively. As shown in Fig. 4, Comparative Example 12 had an amorphous single-phase structure. Also, as shown in Fig. 5, Comparative Example 13 was found to have a structure in which the amorphous phase, which is the main phase, and the α-Fe phase oriented in-plane due to heterogeneous nucleation were mixed in the surface layer. The volume ratio of the amorphous phase calculated from the powder X-ray diffraction results is shown in Table 3.

[0060] As in Examples 1-11, for Comparative Examples 12-15, the saturation magnetic flux density Bs, the core loss (core loss) and magnetic permeability (μ) at a magnetic flux density of 1.5 T at 1 kHz, and the core loss at a magnetic flux density of 1.5 T at 20 kHz were measured, and the results are shown in Table 4. In addition, as a representative example of a comparative example showing the relationship between magnetic flux density and core loss, FIG. 7 shows a plot of the iron-based soft magnetic alloy of Comparative Example 12 for each operating frequency.

[0061] The rapidly solidified alloy of Comparative Example 16 had a Si-less composition and a slow roll surface speed of 10 m / sec, resulting in a coarse metal structure with an average crystal grain size of 100 nm or more, which made it impossible to punch. In Comparative Example 17, the slit width was as wide as 0.9 mm, which increased the tapping rate of the molten metal provided to the surface of the rapidly solidified roll from the single slit, resulting in an average thickness of 40 μm or more as shown in Table 3, and the punching test results were unacceptable.

[0062] 8 shows the relationship between operating frequency and iron loss at a magnetic flux density of 1.5 T for each of Example 2, Comparative Example 12, and a commercially available electrical steel sheet (35A360 manufactured by JFE Corporation). FIG. 9 shows an SEM photograph of the iron-based soft magnetic alloy of Example 2.

[0063] [Table 1]

[0064] [Table 2]

[0065] [Table 3]

[0066] [Table 4] [Explanation of symbols]

[0067] l Single roll molten metal quenching device 2 Melting furnace 3 Molten alloy 4 Tilt axis 5. Hot water container 6. Water outlet nozzle 7 Slit 8. Cooling roll 9 Rapidly solidified alloys

Claims

1. Composition formula (Fe 1-m Co m ) 100-x-y S x (B 1-n C n ) y where the composition ratios x, y, m, and n are expressed as follows: 1.0≦x≦3.0 atomic%, 11.0≦y≦14.0 atomic%, 0.05≦m≦0.5、 0.0≦n≦0.3 preparing a molten alloy having a composition that satisfies the above and does not contain Cu; and a rapid solidification step of rapidly solidifying the molten alloy on a cooling roll made of any one of pure copper, copper alloy, Mo, and W as a main raw material, A method for producing an iron-based soft magnetic alloy having a metal structure consisting of an α-Fe phase, a ratio of an amorphous phase of 20 volume % or less, a saturation magnetic flux density of 1.7 T or more and 2.0 T or less, an iron loss of 50 W / kg or less at a magnetic flux density of 1.5 T and a frequency of 1 kHz, and a thickness of 18 μm or more and less than 40 μm, comprising the steps of: the rapid solidification step includes a step of injecting the molten alloy from a nozzle onto a surface of the chill roll while rotating the chill roll at a roll surface speed of 15 m / sec or more and 50 m / sec or less, the nozzle is a single slit nozzle and is arranged so that the longitudinal direction of the slit is perpendicular to the rotation direction of the cooling roll; The material of the nozzle is mainly composed of any one of quartz (SiO2), boron nitride (BN), silicon carbide (SiC) and alumina (Al2O3), The nozzle has an opening width of 0.2 mm or more and 0.8 mm or less, The surface roughness of the cooling roll is an arithmetic average roughness (Ra) of 0.01 μm or more and 0.6 μm or less, The distance from the nozzle to the cooling roll is 0.1 mm or more and 2.0 mm or less, The method for producing an iron-based soft magnetic alloy includes pouring the molten alloy from the nozzle at a pressure of 5 kPa or more and 50 kPa or less.

2. A method for producing an iron-based soft magnetic alloy as described in claim 1, wherein the iron-based soft magnetic alloy has an iron loss of 1500 W / kg or less at a magnetic flux density of 1.5 T and a frequency of 20 kHz.

3. A method for producing an iron-based soft magnetic alloy as described in claim 1, wherein the average crystal grain size of the α-Fe phase of the iron-based soft magnetic alloy is 5 nm or more and less than 100 nm.

Citation Information

Patent Citations

  • Iron-based amorphous nanocrystalline alloy, preparation method thereof, amorphous iron core and application of amorphous iron core

    CN114974784A

  • Production of metal strip and nozzle for production

    JP1988220950A

  • Production of thin strip of amorphous alloy having large thickness

    JP1993329587A

  • Ferrous amorphous alloy

    JP1995113151A

  • Multilayered magnetic alloy thin strap

    JP1996124731A

Cited By

  • Iron-based soft magnetic alloy and its manufacturing method

    JP7765140B1